Increasing Studentss’ Effetive Reading Speed Competence by Using The Klos Method at SMP Negeri 02 Rumbia, Indonesia Sitti Jumarni Maduha - Sitti Jumarni Maduha (USN Scientific Journal, 2023)
The effective speed of reading has a very important role, because with fast reading accompanied by the ability to understand quality reading one can master science and technology. However, the habit of reading Indonesian that is not good has a negative impact on a person's level of readability, especially a student. To overcome this much needed effort and creativity of the teacher. One of them is through the application of the klos method in learning to read. This study aims to increase the Effective Reading Speed (KEM) using the clos method for Class VIII students of SMP Negeri 02 Rumbia. This classroom action research took place at SMP Negeri 02 Rumbia grade VIII, with a total of 30 students. Implementation of activities carried out through three cycles. Data from the three cycles are in the form of student and teacher observations during the learning process. The entire data was analyzed qualitatively. While the data on the results of the Effective Reading Speed (KEM) test for students using the KLOS method were analyzed quantitatively. The results of the data analysis show that learning speed reading activities using the KLOS method can increase students' Effective Reading Speed (KEM).